Increased Interferon-Induced Protein With Tetracopeptides (IFITs) Reduces Mycobacterial Growth - Madhvi, Abhilasha; Mishra, Hridesh; Chegou, Novel N.; Baker, Bienyameen (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The host immune response towards Mycobacterium tuberculosis is known to vary with the virulence of mycobacterial species. While the majority of M. tb-exposed individuals develop latent TB infection (LTBI), a small proportion develops active TB disease. Milieu of understudied immune factors is believed to play an important role against host-immune response towards mycobacteria. Here, we investigate the role of anti-viral factors of the interferon-induced proteins with tetracopeptides (IFITs) family, which in our previous research, shown to be upregulated in response to pathogenic M. tb, but as yet have no established role in host response to bacterial infections. Methods: We performed vector-driven overexpression and siRNA-mediated downregulation of IFITs in THP-1 cells infected with different mycobacterial species. Also, we investigated the mRNA levels of IFITs in the LTBI and active-TB cases. Results: Overexpression of IFITs reduces CFUs by 32% (30%-43%) [Median (IQR)] across three different mycobacterial strains, while knock-down increases CFUs by 57% (41%-78%). Compared to IFN-γ, treatment of infected THP-1 cells with IFN-β significantly increases the expression of IFITs, while the knock-up of IFITs had higher mRNA expression of IFN-β than IFN-γ. Cytokines like IDO-1, IL-6, IL-23 and IFN- γ are observed to play key role in mycobacterial survival upon IFITs intervention. mRNA expression of IFITs were higher in LTBI cases as compared to active TB. Conclusion: Higher expression levels of IFITs reduces in vitro survival of different drug-susceptible and drug-resistant mycobacteria and correlates with latent TB infection in infected individuals, hence emerging as an immuno-therapeutic target against M. tb.